Analysis Of Twitter's Social Media Usage In Russia-Ukraine War In 2022 - Martin, Ali; Hartati, Anna Yulia; Riyanto, Agus; Ismiyatun, Ismiyatun (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Russia's invasion of Ukraine occurred on February 24, 2022, followed by an information war that occurred on social media. Ukraine, which is inferior in terms of the number of weapons compared to Russia, certainly took advantage of this momentum to win the information war circulating on social media. Therefore, the narrative, in the form of persuasion or pressure, was carried out by official accounts from the Ukrainian government and officials to put pressure on several parties. Twitter is used to win the information war and get support from all parties. There are three Ukrainian targets: foreign governments, foreign companies, and the public. Of course, this is Ukraine's move to be able to attack Russia, especially on the economic front. This study uses qualitative research methods and secondary data. The theory used in this research is international political communication theory